Analisis Pengaruh Konsentrasi Natrium Hidroksida terhadap Sifat Mekanik Biokomposit Berpenguat Serat Sisal - Kusmiran, Amirin; Desiasni, Rita (Jurnal Fisika, 2020)
The mechanical properties of natural fibers are continuous development as the alternatively synthetic fibers because of the natural fibers are non-corrosive, lightweight, and environmental advantages. However, these fibers have poor interfacial adhesion properties as the fibers if used as bio-composite material. This problem can be solved by the surface modification method by the sodium hydroxide treatment used to improve the mechanical properties. A sodium hydroxide concentration which it used at 0 wt%, 5 wt%, 10 wt%, and 15 wt% and the sisal fibers were soaked in that a concentration for 2 hours. Furthermore, the bio-composite fabrication is conducted by hand lay-up technique which is using both sisals as the fibers and epoxy resin as the matrix. The tensile test RTG-1250 results show that the maximum mechanical properties, such as strains, Young's modulus, and elongation, was obtained at sodium hydroxide 5 wt% than others where the values of these mechanical properties were 25.334 MPa, 16.111 GPa, and 1.572%, respectively. The morphological evaluation carried out using a scanning electron microscope showed that the alkali sodium hydroxide treatment was improved interfacial adhesion between fiber and matrix. Finally, sodium hydroxide alkali treatment of more than 5% can be able to sisal fiber cracks so that the mechanical properties of bio-composite can decrease continuously.